Existence Analysis of Multi-Point Boundary Value Problems with Riesz-Caputo Fractional Derivatives - Takieddine Zeghida; Rabah Khaldi; Assia Guezane-Lakoud (Sahand Communications in Mathematical Analysis)
This paper explores the study of a specific category of nonlinear multi-point boundary value problems (BVPs) associated with Riesz-Caputo fractional differential equations and integral boundary conditions. The primary objective is to establish the existence of solutions under specific assumptions. We use Krasnoselskii's fixed point theorem and Leray-Schauder's nonlinear alternative to achieve this goal. Furthermore, numerical examples are presented and plotted to demonstrate the effectiveness of the obtained results.